2006
DOI: 10.1042/bj20060183
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous ADP-ribose enables calcium-regulated cation currents through TRPM2 channels in neutrophil granulocytes

Abstract: International audienceTRPM2 is a Ca 2+}-permeable cation channel gated by ADP-ribose (ADPR) from the cytosolic side. To test whether endogenous concentrations of intracellular ADPR are sufficient for TRPM2 gating in neutrophil granulocytes, we devised an HPLC protocol to determine ADPR contents in perchloric acid cell extracts. The reversed phase ion-pair HPLC protocol with a Mg 2+} containing isocratic eluent allows baseline resolution of one ADPR peak. Intracellular ADPR concentrations were about 5 {mu}M in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
128
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(138 citation statements)
references
References 29 publications
7
128
3
Order By: Relevance
“…Previous studies on TRPM2 in primary neutrophils employed Cs + -based intracellular solutions [12,20], and one study reported the failure of cADPR to activate or synergize with ADPR and AMP to inhibit ADPR-induced TRPM2 currents in human neutrophils [12]. Since these studies provided results under somewhat limited experimental conditions, we conducted a detailed analysis of the facilitatory actions of cADPR, H 2 O 2 and NAADP in relation to ADPR-induced TRPM2 activation in primary human neutrophils, using K + -based solutions and assessing agonist effects over a large concentration range.…”
Section: Regulation Of Trpm2 By Intracellular Ca 2+mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies on TRPM2 in primary neutrophils employed Cs + -based intracellular solutions [12,20], and one study reported the failure of cADPR to activate or synergize with ADPR and AMP to inhibit ADPR-induced TRPM2 currents in human neutrophils [12]. Since these studies provided results under somewhat limited experimental conditions, we conducted a detailed analysis of the facilitatory actions of cADPR, H 2 O 2 and NAADP in relation to ADPR-induced TRPM2 activation in primary human neutrophils, using K + -based solutions and assessing agonist effects over a large concentration range.…”
Section: Regulation Of Trpm2 By Intracellular Ca 2+mentioning
confidence: 99%
“…This is considerably lower than the EC 50 values obtained for heterologously expressed TRPM2 in HEK293 cells (10 μM) [7,16], or native TRPM2 in Jurkat T cells (7 μM) [10], U937 monocytes (40 μM) [4], and RINm5f cells (20 μM, Fleig unpublished observations), indicating that both ionic and cellular environment can determine the sensitivity of TRPM2 channels to ADPR. Several cellular systems have been shown to require the presence of intracellular and/or extracellular Ca 2+ to evoke ADPR-induced TRPM2 currents, including human neutrophils [4,12,[14][15][16]. When perfusing human neutrophils with a fixed concentrations of 1 mM ADPR in the presence of increasing intracellular Ca 2+ concentrations ranging from 0 to 1 μM ( Fig.…”
Section: Regulation Of Trpm2 By Intracellular Ca 2+mentioning
confidence: 99%
See 3 more Smart Citations